URINARY INCONTINENCE IS ASSOCIATED WITH FRAILTY AND GAIT AMONG COMMUNITY-DWELLING ELDERS IN CHINA - Chu, J. (Innov Aging, 2017)
Objective: To examine the association between urinary incontinence and frailty in community-dwelling elders. Methods: A cross-sectional study was conducted in the city of Hangzhou, which leads the growing speed of aging population in China. Severity and symptoms of urinary incontinence (UI) were measured using ICIQ-SF. Participants with positive answer of the question “Did you have problems of urinary incontinence in recent 4 weeks” were categorized as UI positive. Status of frailty was defined by Clinical Frailty Scale (CFS). Participants also completed comprehensive geriatric assessment. Multiple linear regression models were used to determine the associations between UI and frailty. Results: Of the 171 participants (74.8 ± 6.0 years with 45.6% females), 57 individuals (33.3%, with 64.9% females) were UI positive. Elders with UI were more likely to have comorbidity (64.9% vs 45.6%, p=0.023) and polypharmacy (47.4% vs 27.2%, p=0.01), higher risk of malnutrition (MNA-SF: 12.47 ± 1.58 vs 12.98 ± 1.30, p=0.036), poorer hand grip (27.35 ± 8.93 vs 33.49 ± 8.95, p<0.01) and higher CFS (3.47 ± 1.05 vs 3.03 ± 0.60, p<0.01). Among UI positive participants, females and males got similar ICIQ-SF score (p=0.282). As self-reported possible reasons of UI, females leak more often when cough or sneeze (67.6% vs 10.0%, p<0.001), less often after urinating (2.7% vs 45.0%, p<0.001) than males. Multivariate analysis showed that frailty (OR, 2.051; 95%CI, 1.120~2.981; p<0.001) was associated with UI in elderly male. Meanwhile, grip (OR, -0.238; 95%CI, -0.400~-0.076; p=0.005) was associated with UI in elderly female. Conclusion: Frailty and low gait are of great importance for older adults, and may be associated with urinary incontinence.